The Relationship between Study Habits and Learning Outcomes - Wahyuni, Hera; Damayanti , Marisyah; Rasimin (International Journal of Multidisciplinary Applied and Science Research, 2025)
they greatly influence the understanding and learning outcomes they will achieve. This study aims to measure the level of habits and learning outcomes of students at SMP N 21 Batang Hari. The research method uses a quantitative approach with a correlational method and uses a sample of 89 students with the Pearson Product Moment Correlation analysis method to find the direction and strength of the relationship between the research variables. The results of the study show that (1) in general the level of student learning habits that include work methods and punctuality in completing tasks are in the high category with a percentage of 84%. (2) the level of student learning outcomes has an average value of 80 with a percentage of 89% and is in the very high category. (3) the results of this study state that there is a relationship between study habits and student learning outcomes. This relationship is proven by the results of the sig value of 0.019 <0.05 which indicates a relationship between the two variables, and is proven by the results of the calculated r correlation of 0.248. After interpreting the value using the correlation interpretation criteria, the r value (0.248) is in the range (0.21–0.40) which is interpreted as being included in the category of having a correlation